Haemato-Biochemical Studies Before and After Ovario Hysterectomy in Bitches Affected with Pyometra - Hadiya,; Patel, Dipak M.; Parikh, Pinesh V.; Rao, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was conducted on 18 bitches; 10 affected with pyometra and 8 normal healthy bitches to evaluate and compare the haemato biochemical profiles before and after surgical intervention. The blood samples were collected from confirmed cases of canine pyometra  and healthy bitches just before and on day 8th and 15th after surgery. The mean values of haemoglobin, packed cell volume, total  erythrocyte count, total platelet count were significantly (p
Keywords: Bitch; Haematology; Neutering; Ovario-hysterectomy; Plasma Biochemistry; Pyometra